Протокол по проблемам воды и здоровья и Повестка дня на период до 2030 года - United Nations (United Nations, 2020)
The United Nations Economic Commission for Europe (UNECE)-World Health Organization (WHO) Regional Office for Europe Protocol on Water and Health has a key role to play in promoting and operationalizing the achievement of the 2030 Agenda for Sustainable Development (2030 Agenda) in national and regional contexts, by providing valuable experience, concrete tools and a successful regional platform to help propel the implementation of the water, sanitation and health related Sustainable Development Goals (SDGs)forward in an inclusive manner. The Protocol and the 2030 Agenda are mutually reinforcing. While the Protocol is a legally binding tool that goes beyond the SDGs and will continue after 2030, the momentum of the SDGs, which are an international commitment of utmost importance, can be used to promote accession to the Protocol and its implementation, at national, regional and global level, thereby facilitating achievement of the Protocol objectives – universal access to safe drinking water and adequate sanitation. The purpose of this practical guide for joint implementation of the Protocol on Water and Health and the 2030 Agenda is to highlight the benefits of and provide step-by-step guidance for coordinated action.